ANALYSIS OF THEORETICAL AND PRACTICAL CHARACTERISTICS OF PROFIT TAX - Quldoshev Sanjar Sapartoshovich (Web of Journals Publishing, 2024)
The article substantiates the need to categorize costs in the calculation of income tax by economic entities, their classification into economically justified and unjustified costs, analyzes using practical examples, highlights aspects of tax legislation that should be considered in Appendix 2 to the calculation of income tax.
Keywords: operating expenses, classification of costs, economically justified and unjustified expenses, expenses included in the cost of production, current expenses, financial expenses, extraordinary losses, income tax calculation.